Toleransi dalam masyarakat multikultural - Gandhi, Abel Mahardika (Maliki Interdisciplinary Journal, 2026)
Indonesia, renowned for its remarkable diversity, encompasses a rich tapestry of ethnicities, religions, races, cultures, and languages, shaping it into a vibrant multicultural society. This unique societal composition underscores the critical importance of tolerance as a cornerstone for preserving social harmony. The focus of this study is to explore the concept of tolerance within such a multicultural framework, highlight its significance in diverse communities, and analyze its role in fostering a harmonious and peaceful social coexistence. A descriptive qualitative method was employed in the research, utilizing a literature study approach by examining various sources, including books, academic journals, and scholarly articles. The findings affirm that tolerance is vital in cultivating harmonious interpersonal relationships, mitigating conflicts, and promoting unity amidst diversity. Furthermore, integrating tolerance into everyday life across familial, educational, and communal settings can pave the way for a peaceful, inclusive, and thriving society. Consequently, it is imperative to consistently nurture tolerance as an intrinsic part of individual and collective character in social dynamics.